When Proportion Problems Confuse: Prospective Teachers’ Reasoning Difficulties - Parameswari, Pradina; Fitria, Analisa; Labuem, Susana (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
Difficulties in completing school mathematics material are also experienced by prospective teacher students. Proportion is the foundational mathematical material for studying other mathematics. Commonly known proportion concepts are direct and inverse proportion. Most students still have difficulty distinguishing between direct and inverse proportion. To distinguish between two problems requires proportional reasoning. Therefore, this study aimed to describe the forms of proportional reasoning difficulties of prospective teacher students in distinguishing between direct and inverse proportion. This research was a case study which conducted at a private university in Malang City, attended by 10 third-semester students. Two subjects were selected based on mathematics tests, interviews, and student willingness. The results showed that students experienced intuitive, additive, and proportion attempt difficulties in the first problem. Meanwhile, students experienced difficulties with additive and proportion attempts difficulties in the second problem. This research can provide insight into how prospective teacher students effectively teach the concept of proportion.